Peningkatan Inovasi Olahan Buah Menjadi Produk Yang Memiliki Daya Saing Tinggi Pada UKM Pejuang Rasa - Nathania Ariyani Paramesti Anindya; Ni Made Ida Pratiwi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Small and Medium Enterprises (SMEs) are one of several pillars that support the economy in Indonesia. The aim of community service through the Merdeka Entrepreneurial Internship activity is to provide assistance to SME partners, regarding innovation menus, flavors, products, as well as marketing methods via social media. With this service, it is hoped that it can be a solution in improving the welfare of SMEs. The partners who receive assistance in this service are UKM Pejuang Rasa which is located on Jalan Semolowaru No VIII, Sukolilo District, Surabaya City, East Java Province. The methods used in this activity are interviews, problem analysis, production planning, production and promotion. Their Entrepreneurship Internship activities are carried out by approximately 4-5 people per group for a total of 30 working days. After going through the observation stage during the activity, a product was produced in the form of a smoothie bowl which had environmentally friendly paperbowl packaging to become an innovation related to fruit processing at Pejuang Rasa UKM. It is hoped that the results of this product innovation can increase sales and business competitiveness with other SMEs.